Activism against AIDS : at the intersection of sexuality, race, gender, and class - Stockdill, Brett C., 1966- (Lynne Rienner Pub., 2003)
"Brett Stockdill reveals that people living with HIV/AIDs are often multiply oppressed - gay men of color, for example - and explores how interlocking oppressions fragment activism and thus impede AIDS prevention and intervention. Demonstrating that a unified approach to issues of race, class, gender, and sexuality can most effectively combat the AIDS epidemic, he highlights critical links among sociological analysis, public policy, and activism."--Jacket.